An Ethno-pragmatic Analysis of Verbal Indirection in Yoruba - Temitope Michael Ajayi (JURNAL ARBITRER, 2018)
The Yoruba language is one of the richest languages in the world in terms of how words and expressions can be employed beyond their conventional meanings. One way of achieving unconventional meaning of words and expressions in the language is the deployment of verbal indirection which is a strategic avoidance of speaking directly in order to achieve a communicative goal. As phenomenal as this concept is in the Yoruba language and culture, it has not received adequate attention from scholars, particularly in Nigeria. This study therefore attempts an ethno-pragmatic analysis of verbal indirection in Yoruba, within the purview of Hyme's Ethnography of speaking and Brown and Levinson's Face theory. The study observes, contrary to the existing notion that verbal indirection is a face-saving strategy in language, it can be deployed as a face-threatening strategy in the Yoruba language.